DSP Based Vector Control of Five-Phase Induction Using Fuzzy Logic Control - Zakaria Mohamed Salem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2012)
This paper proposes an indirect field oriented controller for five-phase induction motor drives. The controller is based on fuzzy logic control technique. Simulation is carried out by using the Matlab/Simulink package. A complete control system experimentally implemented using digital signal processing (DSP) board. The performance of the proposed system is investigated at different operating conditions. The proposed controller is robust and suitable to high performance five-phase induction motor drives. Simulation and experimental results validate the proposed approaches.DOI: http://dx.doi.org/10.11591/ijpeds.v2i2.217